Accounting for globalization: evaluating the potential effectiveness of country-by-country reporting. (October 2015) - Wójcik, Dariusz
The new European Union Accounting and Capital Requirements directives and the US Dodd-Frank Act include provisions on country-by-country reporting, which significantly improve the availability of geographical information on corporate activities. They are, however, a far cry from the idea of full country-by-country reporting, which involves the publication of simplified financial statements by companies for each country in which they operate. This paper outlines the trajectory of the political struggle for countryby- country reporting, and presents an exploratory analysis of potential effectiveness of different versions of country-by-country reporting in terms of policy objectives, the nature of information, as well as the behavior of users and disclosers. It argues that although partial country-by-country reporting offers benefits for the fight against corruption and the assessment of corporate reputational risks by investors and other stakeholders, full country-by-country reporting could offer a greater value to investors and other users, and make a change in disclosers' behavior more likely.